Case Report: A case of pediatric persistent refractory ITP responsive to avatrombopag - Sau, Antonella; Di Prinzio, Gianfranco; Onofrillo, Daniela; Russo, Anna Caterina; Santoro, Nicole; Di Ianni, Mauro (Frontiers in Immunology, 2025)
Immune thrombocytopenia (ITP) is a rare hematologic disorder characterized by low platelet counts due to an immune-mediated destruction of platelets. While corticosteroids, intravenous immunoglobulin (IVIG) are the mainstays of treatment, a subset of patients may remain refractory to these therapies. Here, we present a case of a 6-year-old girl diagnosed with refractory ITP, who failed to respond to standard therapies but showed a remarkable clinical improvement with avatrombopag, a thrombopoietin receptor agonist.